Ameliorative Role of Cabernet Sauvignon Seed Oil on Hyperlipidemia, Inflammation, and Oxidative Stress in Mice. Issue 10 (20th August 2019) - Li, Xiaojing; Shen, Yingbin; Tang, Na; Zhu, Jianhong; Xiao, Junyong; Cong, Renhuai; Zhang, Hui; Wu, Gangcheng; Qi, Xiguang
Abstract : Virgin Cabernet Sauvignon grape seed oil (VGSO) contains high levels of linoleic acid (74%), and total unsaturated fatty acids amount to about 88%. In comparison to other edible oils, VGSO also contains an abundance of endogenous antioxidants, such as tocopherols, tocotrienols, and phenolic compounds, the consumption of which has been positively associated with improvements in health status. This study is the first to investigate regulatory mechanisms of VGSO on hyperlipidemia in mice fed a high‐fat diet via exploration of changes in the expression patterns of genes associated with lipid metabolism. Results show that liver CAT and GSH‐px levels are higher and liver MDA concentrations are lower in the VGSO group as compared to those of CO and LO groups. In addition, concentrations of liver pro‐inflammatory cytokines are significantly decreased in mice fed VGSO, likely associated with the down‐regulation of TNF‐α and IL‐6. In addition, hyperlipidemia in mice can be ameliorated by consumption of VGSO through the up‐regulation of PPARα expression and down‐regulation of the expressions of SREBP‐1c, ACC, and FAS. In addition, findings also suggest that unsaponifiables are the most important factor in regulating lipid metabolism and protecting the liver. Practical Applications : Virgin Cabernet Sauvignon grape seed oil (VGSO) is rich in linoleic acid, phytosterols, tocopherols/tocotrienols, and phenolic compounds. VGSO has been reported to have the potential beneficial effects on hyperlipidemia. This study further investigates regulatory mechanisms of VGSO on hyperlipidemia in mice fed a high‐fat diet via exploration of changes in the expression patterns of genes associated with lipid metabolism. This study also investigates the effect of VGSO on improving inflammation and oxidative stress in mice and key component of VGSO for regulating lipid metabolism and protecting the liver. This research will provide a theoretical basis for the development of functional grape seed oil. Virgin grape seed oil (VGSO) is produced to increase added values of the wine industry due to the fact that it contains high level of unsaturated fatty acids and endogenous antioxidants. This study investigates the effect of VGSO on mice fed a high‐fat diet, and finds that VGSO can improve inflammation in mice via down‐regulation of TNF‐α and IL‐6 expression. Abstract : Virgin grape seed oil (VGSO) is produced to increase added values of the wine industry due to the fact that it contains high level of unsaturated fatty acids and endogenous antioxidants. This study investigates the effect of VGSO on mice fed a high‐fat diet, and finds that VGSO can improve inflammation in mice via down‐regulation of TNF‐α and IL‐6 expression.